Question
upstudy study bank question image url

Solve for \( u \). \[ 3+\frac{1}{u+6}=-\frac{5}{(u+1)(u+6)} \] If there is more than one solution, separate them with commas. If there is no solution, click on "No solution". \( u=\square \square \)

Ask by Beck Mann. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( u = -\frac{4}{3} \)

Solution

To solve the equation   3 + 1/(u + 6) = -5/((u + 1)(u + 6)), we first note that u ≠ -6 and u ≠ -1 (to avoid division by zero). Step 1. Multiply both sides of the equation by (u + 1)(u + 6) (valid since u avoids -1 and -6):   3(u + 1)(u + 6) + (u + 1) = -5. Step 2. Expand (u + 1)(u + 6):   (u + 1)(u + 6) = u² + 7u + 6. Substitute back:   3(u² + 7u + 6) + (u + 1) = -5. Step 3. Expand and combine like terms:   3u² + 21u + 18 + u + 1 = 3u² + 22u + 19. So, we have:   3u² + 22u + 19 = -5. Step 4. Bring -5 to the left side:   3u² + 22u + 19 + 5 = 3u² + 22u + 24 = 0. Step 5. Solve the quadratic equation 3u² + 22u + 24 = 0. Calculate the discriminant:   D = 22² - 4·3·24 = 484 - 288 = 196, and √D = 14. Step 6. Use the quadratic formula:   u = (-22 ± 14) / (2·3). This gives two potential solutions:   u = (-22 + 14) / 6 = (-8) / 6 = -4/3,   u = (-22 - 14) / 6 = (-36) / 6 = -6. Step 7. Reject any extraneous solutions: Since u = -6 makes a denominator zero in the original equation, we must discard it. Thus, the valid solution is:   u = -4/3.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve the equation \[ 3+\frac{1}{u+6}=-\frac{5}{(u+1)(u+6)}, \] we'll first eliminate the fractions by multiplying both sides by \( (u+1)(u+6) \): \[ 3(u+1)(u+6) + (u+1) = -5. \] This expands to: \[ 3(u^2 + 7u + 6) + (u + 1) = -5. \] Distributing the 3 yields: \[ 3u^2 + 21u + 18 + u + 1 = -5. \] Combine the like terms: \[ 3u^2 + 22u + 19 = -5. \] Now, add 5 to both sides: \[ 3u^2 + 22u + 24 = 0. \] Next, we can use the quadratic formula: \[ u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} = \frac{-22 \pm \sqrt{22^2 - 4 \cdot 3 \cdot 24}}{2 \cdot 3}. \] Calculating the discriminant: \[ 22^2 = 484, \] and \[ 4 \cdot 3 \cdot 24 = 288. \] So the discriminant is: \[ 484 - 288 = 196. \] Now, taking the square root gives: \[ \sqrt{196} = 14. \] Now substituting back into the formula: \[ u = \frac{-22 \pm 14}{6}. \] Calculating the two possibilities for \( u \): 1. For \( u = \frac{-22 + 14}{6} = \frac{-8}{6} = -\frac{4}{3} \). 2. For \( u = \frac{-22 - 14}{6} = \frac{-36}{6} = -6 \). Thus, the solutions are: \[ u = -\frac{4}{3}, -6. \] Therefore, the final answer is: \( u = -\frac{4}{3}, -6 \)

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy